Growing Strawberries in the Florida Home Garden - Vance M. Whitaker; Natalia Peres; Sriyanka Lahiri; Sydney Park Brown; Craig K. Chandler (EDIS, 2021)
Florida is the winter strawberry capital of the world. In commercial and home production, strawberries are grown as an annual crop rather than as perennials. This 4-page publication of the UF/IFAS Horticultural Sciences Department presents guidelines for the successful production of strawberries in the Florida home garden. Minor revision with an updated byline of Chandler, C. K., N. A. Peres, V. M. Whitaker, H. A. Smith, and S. P. Brown. 2014. "Growing Strawberries in the Florida Home Garden." EDIS 2008 (6).